2008
DOI: 10.1161/atvbaha.107.158725
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Role of VEGF-B Suggests a Restricted Role in the Revascularization of the Ischemic Myocardium

Abstract: Objective— The endogenous role of the VEGF family member vascular endothelial growth factor-B (VEGF-B) in pathological angiogenesis remains unclear. Methods and Results— We studied the role of VEGF-B in various models of pathological angiogenesis using mice lacking VEGF-B (VEGF-B −/− ) or overexpressing VEGF-B 167 . After occlusion of the left coronary artery, VEGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
102
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 27 publications
3
102
2
1
Order By: Relevance
“…63 , 69 Gene knockout studies showed that VEGF-B does participate in coronary vasculature development and normal physiological responses to ischemia and vascular occlusion. 18 And, the HF patients showed the declined VEGF-B, 70 both in ischemic and dilated cardiomyopathy. Mice lacking VEGF-B displayed mild cardiac phenotypes, such as the slightly smaller heart and dysfunctional coronary vasculature in Bellomo VEGF-B −/− mice 67 and a prolonged PQ interval in Aase VEGF-B −/− mice.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…63 , 69 Gene knockout studies showed that VEGF-B does participate in coronary vasculature development and normal physiological responses to ischemia and vascular occlusion. 18 And, the HF patients showed the declined VEGF-B, 70 both in ischemic and dilated cardiomyopathy. Mice lacking VEGF-B displayed mild cardiac phenotypes, such as the slightly smaller heart and dysfunctional coronary vasculature in Bellomo VEGF-B −/− mice 67 and a prolonged PQ interval in Aase VEGF-B −/− mice.…”
Section: Introductionmentioning
confidence: 95%
“…Subsequent studies, however, argued against the angiogenic activity of this molecule. 15-18 Physiologically, VEGF-B has little growth effects, as demonstrated in gain-of-function studies using transgenic 15 and adenoviral 16 expression of VEGF-B models and loss-of-function studies using VEGF-B null mice. 17 , 18 Under pathological conditions, this molecule can prevent cells from apoptosis and death.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations